Love, Creekwood : a Simonverse Novella - Albertalli, Becky (Albertalli, Becky. Simonverse., 2020)
It's been more than a year since Simon and Blue turned their anonymous online flirtation into an IRL relationship, and just a few months since Abby and Leah's unforgettable night at senior prom. Now the Creekwood High crew are in their first years at different colleges, navigating friendship and romance the way their story began-- on email.